THE INFLUENCE OF THE EXTERNAL ENVIRONMENT AND MANAGERIAL FACTORS ON THE FINANCIAL PERFORMANCE OF MSMES THROUGH STRATEGIC PLANNING - Pratama Putra, Satria; Dwi Ayu Parmitasari, Rika; Rusnawati (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2025)
Increasingly tight business competition requires Micro, Small, and Medium Enterprises (MSMEs) to be more adaptive in facing changes in the external environment and improving managerial capabilities in order to achieve optimal financial performance. This study aims to analyze the influence of the external environment and managerial factors on the financial performance of MSMEs in Makassar City with strategic planning as an intervening variable. A quantitative approach was used in this study with a survey method involving MSMEs in the food and beverage sector that have been operating for at least two years. The purposive sampling technique was applied in selecting the sample. Data analysis was carried out using the Structural Equation Modeling (SEM) method to test the relationship between the variables studied. The results of the study indicate that the external environment and managerial factors have a significant effect on the financial performance of MSMEs, with strategic planning as an intervening variable that strengthens the relationship. This finding emphasizes the importance of adapting to business dynamics and improving managerial quality and strategic planning for the sustainability and growth of MSMEs. Therefore, developing strategies based on external environmental analysis and strengthening internal competencies are the keys to increasing the competitiveness of MSMEs in facing changing market challenges.